Pengembangan E-Book Materi Jual Beli dengan Pendekatan Matematika Realistik Berbasis Kearifan Lokal Suku Dayak Kalimantan Tengah untuk Mengatasi Cognitive Load - Yukti Sari, Rospala Hanisah; Rezki, Istighfaris (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2024)
Overcoming cognitive load is very necessary so that the learning material delivered by teachers can be constructed by students, so that students gain meaningful knowledge and experience. Thus, learning mathematics using a Realistic Mathematics Education approach based on the local wisdom of the Dayak Tribe is important to apply to overcome the cognitive load of students in Central Kalimantan. The objectives of this research are 1) To find out whether e-book buying and selling material using a Realistic Mathematics Education approach based on local Dayak wisdom can meet the criteria for being suitable for use; 2) To find out whether e-book buying and selling material using a Realistic Mathematics Education approach based on local Dayak wisdom can overcome the cognitive load of students in Central Kalimantan. This research uses the Research and Development (RnD) method with a 4-D model developed by Thiagarajan. The development steps are definition, design, development and dissemination. The data collection technique is a Likert Scale to determine whether the product being developed meets feasibility. The research results show that 1) e-book buying and selling material using a Realistic Mathematics Education approach based on local Dayak wisdom meets the appropriate criteria; 2) e-book buying and selling material with a Realistic Mathematics Education approach based on local Dayak wisdom can overcome the cognitive load of students in Central Kalimantan